2013
DOI: 10.1155/2013/402096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Suppurative Osteomyelitis, Bisphosphonate-Related Osteonecrosis, and Osteoradionecrosis: Report of Three Cases and Review of the Literature

Abstract: In the past, osteomyelitis was frequent and characterized by a prolonged course, treatment response uncertainty, and occasional disfigurement. Today, the disease is less common; it is believed that the decline in prevalence may be attributed to increased availability of antibiotics and improvement of overall health patterns. Currently, more common osteomyelitis variants are seen, namely, osteoradionecrosis (ORN) and bisphosphonate-related osteonecrosis of the jaws (BRONJ). Osteomyelitis, ORN, and BRONJ can pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
(33 reference statements)
0
14
0
1
Order By: Relevance
“…This study aimed to evaluate the histopathological aspects of OMJ, ORNJ, and MRONJ considering close similarities among them and, consequently, to make clinicians aware of the importance of understanding the etiopathogenesis and clinical manifestations of each disease. Few studies with the same objectives were found in a recent review of the literature; 1,3,10,11 but more information was needed in order to clarify histological differences between the diseases. It is important to emphasize that the pathologies chosen in the present study had already been diagnosed based upon the patients' clinical information given by the clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aimed to evaluate the histopathological aspects of OMJ, ORNJ, and MRONJ considering close similarities among them and, consequently, to make clinicians aware of the importance of understanding the etiopathogenesis and clinical manifestations of each disease. Few studies with the same objectives were found in a recent review of the literature; 1,3,10,11 but more information was needed in order to clarify histological differences between the diseases. It is important to emphasize that the pathologies chosen in the present study had already been diagnosed based upon the patients' clinical information given by the clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, particular attention is given to osteomyelitis (OMJ), osteoradionecrosis (ORNJ), and medication-related osteonecrosis of the jaw (MRONJ). 1,2,3 However, it is important to emphasize Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. that these are quite distinct clinical pathologies with different etiologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per protocol, all the indicated teeth should be extracted 21 days before initiation of radiation therapy and patients should be instructed on meticulous oral hygiene and fluoride should be applied to the dentition daily via custom molded trays and should undergo weekly check-up during RT and monthly follow-ups for the first 6 months and then following early post-treatment patient should visit their dentists for every 4 months. [33] Osteoradionecrosis is a disease that requires excessive consideration and a multidisciplinary association, which involves the patient, general dentists, specialist in maxillofacial surgery and specialist in oncology and RT.…”
Section: Discussionmentioning
confidence: 99%
“…Other trauma, mechanical injuries, poor dental status etc. can induce the necrosis as well [1][2][3][4][5][6][7][8][9][10] . Sometimes, in less than 10%, ORN occurs spontaneously 11 .…”
Section: Introductionmentioning
confidence: 99%